A Study Of Infant Mortality In Field Practice Area Of Kasturba Medical College, Manipal - A Preliminary Analysis - Chakladar B.K; Udaya Kiran N; Krishnan Lalitha; Phaneendra Rao R.S (Wolters Kluwer Medknow Publications, 1987)
A retrospective study was carried out during 1983-84 in the field practice area of Kasturba Medical College, Manipal to determine the infant mortality rate and the factors influencing it. The population covered was 29,519 and infant mortality rate was found to be 24.54. As the sample size was small, a separate study was carried out through Anganwadi workers which covered a larger population of 1,30,906 in the same taluka and the infant mortality rate was found to be 37.8. Searching for the causes of this low infant mortality rate the probable factors were found to be high female literacy health care facilities and its utilization by the people. The age and causes of infant support of the survey findings. Two thirds of the deaths occurred in the neonatal period. The majority of infant deaths were primarily due to infections resulting from environmental influence. The results of the hospital based data indirectly support the finding of low infant mortality rate.